2021
DOI: 10.3390/pharmaceutics13111841
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Nanoparticles Mitigate Macrophage Inflammation via Inhibition of PAMP Interactions and Lactate-Mediated Functional Reprogramming of NF-κB and p38 MAPK

Abstract: Inflammation is a key homeostatic process involved in the body’s response to a multitude of disease states including infection, autoimmune disorders, cancer, and other chronic conditions. When the initiating event is poorly controlled, severe inflammation and globally dysregulated immune responses can occur. To address the lack of therapies that efficaciously address the multiple aspects of the dysregulated immune response, we developed cargo-less immunomodulatory nanoparticles (iNPs) comprised of poly(lactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…This finding is consistent with a previous study on the effect of ATL‐III in a human mast cell inflammation model 38 . MAPK signaling also participates in activating the transcription factor NF‐κB 25,26 . Different studies have found that the activation of p38 and JNK contributes to the production of proinflammatory factors in activated microglia 39 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with a previous study on the effect of ATL‐III in a human mast cell inflammation model 38 . MAPK signaling also participates in activating the transcription factor NF‐κB 25,26 . Different studies have found that the activation of p38 and JNK contributes to the production of proinflammatory factors in activated microglia 39 .…”
Section: Discussionsupporting
confidence: 92%
“…The levels of phosphorylated IκBα and p65, which are involved in the NF-κB signaling pathway, were significantly attenuated by ATL-III administration both in vivo and in vitro (p < 0.05; Figure7A,B). JNK, p38, and ERK1/2 are known to activate NF-κB, which participates in the expression of multiple proinflammatory factors [24][25][26]. As shown in Figure7(C,D), ATL-III did not affect F I G U R E 4 ATL-III regulated the M1/M2 polarization of microglia/macrophages in rats after SCI.…”
mentioning
confidence: 86%
“…To determine if the modification of SAHA affected its anti-inflammatory properties, BMMØs were treated with a subcytotoxic concentration of SAHA (0.01 μM) or SAHA-OH (0.01 μM) for 3 h before the addition of LPS (100 ng/mL) for 48 h. Subsequently, cell culture supernatants were collected and assayed using a Luminex bead-based immunoassay to measure cytokine secretions. , Cytokine analysis revealed that SAHA and SAHA-OH similarly reduce IL-6 (Figure A), TNFα (Figure B), IFNβ (Figure C), IL-1β (Figure D), IL-10 (Figure E), and MCP-1 (CCL2) (Figure F) secretions. Interestingly, SAHA-OH significantly reduced GROα (CXCL1) levels compared to SAHA and LPS controls (Figure G).…”
Section: Resultsmentioning
confidence: 99%
“…Monomeric lactic acid acts as a potent signaling molecule, transcending its role as simply a metabolite both in inflammation and cancer biology 58,59 . In cancer biology, lactate plays as immunomodulatory role 60 .…”
Section: Discussionmentioning
confidence: 99%